2007
DOI: 10.1086/519999
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Deletion and Translocation Breakpoints in 1q44 Implicates the Serine/Threonine Kinase AKT3 in Postnatal Microcephaly and Agenesis of the Corpus Callosum

Abstract: Deletions of chromosome 1q42-q44 have been reported in a variety of developmental abnormalities of the brain, including microcephaly (MIC) and agenesis of the corpus callosum (ACC). Here, we describe detailed mapping studies of patients with unbalanced structural rearrangements of distal 1q4. These define a 3.5-Mb critical region extending from RP11-80B9 to RP11-241M7 that we hypothesize contains one or more genes that lead to MIC and ACC when present in only one functional copy. Next, mapping of a balanced re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
161
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(172 citation statements)
references
References 41 publications
10
161
0
1
Order By: Relevance
“…4,6,7,9,11,18 After chromosomal microarray testing has been available for the identification of submicroscopic chromosomal aberrations, many patients with submicroscopic deletions of 1q44 have been identified. 8,10,12,14,15 Now, precise genotype-phenotype correlation has been evaluated through the accumulation of patients with variable deletion sizes, and a minimal essential region has been proposed for expressing the main characteristics of 1q44 deletion syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,6,7,9,11,18 After chromosomal microarray testing has been available for the identification of submicroscopic chromosomal aberrations, many patients with submicroscopic deletions of 1q44 have been identified. 8,10,12,14,15 Now, precise genotype-phenotype correlation has been evaluated through the accumulation of patients with variable deletion sizes, and a minimal essential region has been proposed for expressing the main characteristics of 1q44 deletion syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,12,14,15 Now, precise genotype-phenotype correlation has been evaluated through the accumulation of patients with variable deletion sizes, and a minimal essential region has been proposed for expressing the main characteristics of 1q44 deletion syndrome. 7,8,[14][15][16] Ballif et al 17 evaluated 22 patients with small interstitial deletions of 1q44 and demonstrated critical regions for microcephaly, ACC and seizures. Consequently, AKT3 was reported to be the gene responsible for microcephaly; zinc finger protein 238 gene (ZNF238) for ACC; and heterogeneous nuclear ribonucleoprotein U gene (HNRNPU) for seizures 17 ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest that selective inhibition of AKT1 may be an effective therapy for cancer. However, in the postnatal brain, AKT3 appears to be the critical isoform, as deletion in mice results in decreased brain size (Easton et al, 2005), whereas in humans, haploinsufficiency of AKT3 has been associated with postnatal microcephaly (Boland et al, 2007). It remains unclear, which AKT isoform is the critical effector downstream of deregulated PI3K signaling in brain tumors.…”
Section: Pi3k Pathway Involvement In Brain Tumorsmentioning
confidence: 99%
“…Interestingly, deletion of the distal end of human chromosome-1q is linked to microcephaly with agenesis of the corpus callosum (e.g. [9][10][11], and a critical region contains only a handful of genes, including RP58. 9-12 RP58, also known as ZNF238, 13 encodes a transcription factor with a BTB/POZ and four zincfinger domains 14 that is highly conserved (495%) between humans and mice, suggesting conserved functions.…”
mentioning
confidence: 99%